Research-to-action multidisciplinary projects: an undergraduate convergence research course - Kimberly Bourne; Jay Rickabaugh; Mike Hambourger; Vicky Klima; Matthew C. Ogwu; Grace Plummer; Robert Swarthout; Jake Siegel; Christine Ogilvie Hendren (Humanities & Social Sciences Communications)
Abstract This paper presents the Research-to-Action Multidisciplinary Project (RAMP) course, a model for training both undergraduates and faculty in convergence research. Competencies needed to achieve convergence are still emerging as part of the literature. As they emerge, faculty and students need new ways to learn these competencies as traditional, unidisciplinary education does not provide these opportunities. This can only happen through an opportunity for hands-on, applied learning. The RAMP course addresses wicked problems through related group projects to facilitate faculty and student co-development of meta-cognitive skills for integration across disciplines. Through faculty interviews, this paper evaluates the success of the RAMP course model in helping faculty develop their own convergence research skills needed to integrate knowledge across disciplines in diverse teams. The RAMP model offers a promising approach to undergraduate convergence research education that equips both students and faculty with essential convergence skills for real-world problem-solving. However, challenges do exist in this model at the institutional, faculty, course design, and course implementation levels. Institutional barriers include bureaucratic hurdles to interdisciplinary team teaching as well as securing project funding. Overcoming these hurdles requires carving new institutional pathways, investing in integrative roles, and leveraging shared, interdisciplinary funding opportunities. By tackling challenges at institutional and organizational levels, the model can be improved to maximize the beneficial outcomes for faculty and students.